PENGARUH STRES KERJA DAN BEBAN KERJA TERHADAP KELELAHAN KERJA PADA KARYAWAN TAMBANG DI PT KARYA MEGAH BUTON - Diman, Diman Diman; Suwarto, Suwarto; Wonua, Almansyah Rundu (Bisnis-Net, 2024)
This research aims to identify: the relationship between work stress and work fatigue among mining employees at PT Karya Megah Buton; and the relationship between workload and work fatigue among mining employees at PT Karya Megah Buton. The approach used is quantitative, with data collected through interviews, literature studies, and the distribution of questionnaires. The research sample consists of 30 production employees from PT Megah Buton. The validity and reliability of the research instruments were tested using SPSS 22.0. Data analysis was conducted using Smart PLS 4.0 for the outer and structural models. The results of the study indicate that work stress not significant effect on work fatigue, with a t-statistic value of 1.578 and a p-value of 0.58. In contrast, workload has a positive and significant effect on work fatigue, with a t-statistic value of 3.329 and a p-value of 0.000.